2016
DOI: 10.1038/srep32537
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of plant defense responses to herbivores by simultaneous recognition of different herbivore-associated elicitors in rice

Abstract: Induced plant defense responses against insect herbivores are triggered by wounding and/or perception of herbivore elicitors from their oral secretions (OS) and/or saliva. In this study, we analyzed OS isolated from two rice chewing herbivores, Mythimna loreyi and Parnara guttata. Both types of crude OS had substantial elicitor activity in rice cell system that allowed rapid detection of early and late defense responses, i.e. accumulation of reactive oxygen species (ROS) and defense secondary metabolites, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 56 publications
3
59
0
1
Order By: Relevance
“…However, S. litura OS treated leaves displayed more pronounced YFP signals than controls ( Figure 1B). This observation confirms previous findings that herbivore stress activates more intense JA defense responses than by wounding alone (Shinya et al 2016). …”
Section: Yellow Fluorescent Protein (Yfp) With a Nuclear Localizationsupporting
confidence: 82%
“…However, S. litura OS treated leaves displayed more pronounced YFP signals than controls ( Figure 1B). This observation confirms previous findings that herbivore stress activates more intense JA defense responses than by wounding alone (Shinya et al 2016). …”
Section: Yellow Fluorescent Protein (Yfp) With a Nuclear Localizationsupporting
confidence: 82%
“…Compared with mock‐treated controls, all tested OsPeps promoted the accumulation of reactive oxygen species (ROS) (Figures b and S1a) and also that of p ‐coumaroylputrescine (CoP), which is a well‐characterized herbivory‐induced secondary metabolite in rice (Alamgir et al ., ) (Figures c and S1b). While the application of OsPep consistently triggered accumulation of CoP it did not significantly increase levels of momilactone B (MB), a typical diterpene phytoalexin of rice previously shown to be weakly induced by herbivory (Figures c and S1b) (Alamgir et al ., ; Shinya et al ., ). This was in contrast to the fungal elicitor (GlcNAc) 8 which strongly induced both CoP and MB in cultured rice cells.…”
Section: Resultsmentioning
confidence: 97%
“…Under such circumstances, and despite some limitations resulting from cultivation in the presence of the growth hormone 2,4‐dichlorophenoxyacetic acid (2,4‐D), rice cell culture systems can be used as an alternative approach. In particular, such a system allows direct application of the desired elicitors to the cells (Shinya et al ., ), and this was considered a major advantage of the current study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The response of a plant to herbivory depends on various factors, such as the ability to recognize the chemical elicitors in the saliva of the insect, and the type of feeding injury (Bonaventure, 2012;Shinya et al, 2016). The PCA indicated that the sesquiterpenes were related to the chemical profile of T. limbativentris-damaged plants.…”
Section: Discussionmentioning
confidence: 99%